Coarse-grained molecular dynamics and continuum models for the transport of protein molecules - Bacci, Marco (Premio Tesi di Dottorato, 2014)
The present work makes use of coarse-grained molecular dynamics simulations and continuum models to investigate the behavior of biomolecules in experiments such as mechanical pulling and driven transport across nanopores. The approach reproduces the wide phenomenology of experiments and allows one to maintain the main features of the transport by modeling the process as a 1D dynamics in a suited potential of the mean force. The standard 1D continuum view is enriched by proposing a model for the description of the shape of isolated molecules based on a tensorial representation and Cauchy-Born rule. Results indicate limitations for unconstrained dynamics and appropriateness for driven ones.